An experimental investigation of the energetic performances of HFO1234yf and its binary mixtures with HFC134a in a household refrigerator. (April 2017) - Aprea, C.; Greco, A.; Maiorino, A.
Highlights: Substitution of HFC134a in a household refrigerator A new generation of low GWP refrigerant fluids: the hydrofluoroolefins (HFOs) HFO1234yf/HFC134a mixture (90/10% weight) as a drop-in substitute of HFC134a The mixture ensures an energy saving of 16 and 14% with respect to HFC134a and HFO1234yf, respectively. Abstract: In this paper, a comparative experimental analysis between HFC134a, HFO1234yf and a refrigerant mixture of HFC134a/HFO1234yf (10/90% weight) implemented in a domestic refrigerator is introduced. Adding 10% of HFC134a to HFO1234yf, the mixture becomes non-flammable with GWP still less than 150. The experimental tests have been conducted under sub-tropical conditions in accordance with the UNI-EN-ISO15502 standard. Two kinds of tests have been shown: pull down and 1-day energy consumption. The results show that HFC134a/HFO1234yf (10/90% weight) is the best drop-in refrigerant fluid for HFC134a in the domestic refrigerator used for the experimental tests. The refrigerant mixture has the closest behaviour to that of HFC134a in terms of temperatures and pressures. Furthermore, the cycle working with the optimal charge of the mixture shows an energy saving of 16 and 14% with respect to HFC134a and HFO1234yf, respectively.